The Effectiveness of Jalin Matra Penanggulangan Kerentanan Kemiskinan Programme in Village of Ngroto - Yeni Nurmawati; Thomas Soseco (Jurnal Ekonomi dan Studi Pembangunan, 2017)
Poverty always appears in the middle of society, especially in the developing countries. Poverty occurred due to people are powerless to come out from poverty problems they face. This condition, indeed, will be a burden in the development process, thus it needs many efforts and attempts to cope with poverty. In order to improve effectiveness towards poverty overcoming strategy and to improve people economy, the government of East Java Province re-established Jalin Matra PK2 (The Other Way to be Independent and Prosperous towards Poverty Vulnerability Overcoming) Programme. This study is a qualitative research using descriptive analysis. The research result showed that: 1) For 29 households (59.19%) stated that there was the increase of income after gaining financing loan, thus the effectiveness of Jalin Matra PK2 Program seen from income aspect run less effectively. The change of income affected by many factors such as the increase of consumption towards target households which influenced by number of family member and more various household needs, also capital or financial needs to sustain the business; 2) For 32 households (65.31%) stated that there was the increase of business turnover after gaining financing loan, thus the effectiveness of Jalin Matra PK2 Program seen from production aspect run effectively. The majority of targeted households able to improve their business; 3) From 477 targeted households listed in almost poor household, so far, that able to get loan was 49 households (10.27%), thus the effectiveness of Jalin Matra PK2 Program seen from financing aspect not run yet effectively.Keywords: Poverty, Effectiveness, Jalin Matra PK2JEL Classification: I31, I38